A covalent organic framework inorganic semiconductor composite material with photocatalytic performance and a preparation method and application thereof

CN122974374APending Publication Date: 2026-10-27GUANGXI TEACHERS EDUCATION UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610947104.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但是,由于单一的COFs材料内部激子结合能较高,致使光生电子-空穴对复合速率较快,从而限制了光催化产H2O2活性

Benefits of technology

1. 本发明的共价有机框架无机半导体复合材料中,共价有机框架材料BTTp负载在硫化铟锌表面,显著提高光催化产H2O2活性,共价有机框架材料的负载率(质量百分占比)为10~15%,在可见光的照射下,对于纯水催化产H2O2的催化效率大幅度提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974374A_ABST
    Figure CN122974374A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of photocatalytic materials, and particularly discloses a covalent organic framework inorganic semiconductor composite material with photocatalytic performance and a preparation method and application thereof. The covalent organic framework inorganic semiconductor composite material is a BTTp-COF / ZnIn2S4 composite material, the mass percentage of ZnIn2S4 in the composite photocatalytic material is 80-90%, the mass percentage of the BTTp-COF is 10-20%, and the synthesis raw materials of the BTTp-COF include 4,4'-(5,6-difluorobenzo[c][1,2,5]thiadiazole-4,7-diyl)diphenylamine and 2,4,6-trihydroxy-1,3,5-benzene triformaldehyde. In the covalent organic framework inorganic semiconductor composite material, the BTTp is loaded on the surface of indium zinc sulfide, the photocatalytic H2O2 production activity is significantly improved, the loading rate of the covalent organic framework material is 10-15%, and under the irradiation of visible light, the catalytic efficiency for the pure water catalytic H2O2 production is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalytic materials technology, and in particular to a covalent organic framework inorganic semiconductor composite material with photocatalytic properties, its preparation method and application. Background Technology

[0002] Hydrogen peroxide (H2O2), as a green and strong oxidant, has shown broad application prospects in pollution control, environmental protection, and drug synthesis. Currently, H2O2 is mainly synthesized via the anthraquinone method, which requires high temperature and pressure conditions, resulting in high energy consumption and certain hazards. Photocatalysis, with its advantages of abundant energy sources, cleanliness, and mild reaction conditions, is an effective green alternative for H2O2 synthesis. As early as 1980, Rao et al. first used metal oxides (ZnO and TiO2) for photocatalytic H2O2 synthesis and achieved good progress. Since then, a large number of inorganic semiconductors have been developed for photocatalytic H2O2 production, such as g-C3N4, BiVO4, WO3, and metal sulfides (ZnIn2S4). Among them, zinc indium sulfide (ZnIn2S4, ZIS) has attracted much attention due to its suitable energy level structure, abundant active sites, and simple preparation method. However, pure ZIS has a narrow visible light response range, can only absorb and utilize light smaller than 500 nm, and has a low light utilization rate; the recombination rate of photogenerated carriers is fast, making it difficult to achieve effective separation and migration of photogenerated electrons and holes; and it has poor stability, making it impossible to recycle.

[0003] Establishing composite systems is an effective strategy to compensate for the defects of inorganic semiconductors and improve their performance. Covalent organic frameworks (COFs) are organic framework materials with 2D or 3D structures, composed of light elements (C, H, O, N, B, etc.) linked by covalent bonds. COFs have significant advantages in the photocatalytic production of hydrogen peroxide. By selecting different building blocks and connection methods, the band structure, light absorption range, and charge separation efficiency of COFs can be precisely controlled, thereby optimizing their photocatalytic activity. However, due to the high exciton binding energy inside single COF materials, the recombination rate of photogenerated electron-hole pairs is relatively fast, thus limiting the photocatalytic activity for H2O2 production. Therefore, constructing a COF and ZIS composite system, allowing electrons and holes to be spatially separated and accumulated separately at active sites on the surfaces of different materials, can effectively improve photocatalytic efficiency. Summary of the Invention

[0004] To address the above shortcomings, this invention provides a covalent organic framework inorganic semiconductor composite material with photocatalytic properties, its preparation method, and its application. The composite material is obtained by loading a covalent organic framework material onto indium zinc sulfide, thereby improving the activity and efficiency of photocatalytic H2O2 production. The specific technical solution is as follows: A covalent organic framework inorganic semiconductor composite material with photocatalytic properties, wherein the composite material is a BTTp-COF / ZnIn2S4 (ZIS) composite material, wherein the BTTp-COF is supported on the surface of ZnIn2S4, the mass percentage of ZnIn2S4 in the composite photocatalytic material is 80-90%, the mass percentage of BTTp-COF is 10-20%, and the raw materials for the synthesis of BTTp-COF include 4,4'-(5,6-difluorobenzo[c][1,2,5]thiadiazole-4,7-diyl)diphenylamine and 2,4,6-trihydroxy-1,3,5-benzenetrialdehyde.

[0005] In the optimized covalent organic framework inorganic semiconductor composite material, the mass percentage of ZnIn2S4 in the composite photocatalytic material is 85%, and the mass percentage of BTTp-COF is 15%.

[0006] On the other hand, the present invention also provides a method for preparing the above-mentioned covalent organic framework inorganic semiconductor composite material, comprising the following steps: (1) Disperse indium zinc sulfide and solvent by ultrasonication for 5-15 min; (2) Add 4,4'-(5,6-difluorobenzo[c][1,2,5]thiadiazole-4,7-diyl)diphenylamine (BT-2F) and 2,4,6-trihydroxy-1,3,5-benzenetriformaldehyde (Tp) in sequence, continue sonication for 5~10 min, then add acetic acid and sonicate to mix; after multiple cycles of freezing-degassing, react in a vacuum environment at 110~130℃ for 65~75 h; (3) After the reaction is complete, wash and vacuum dry to obtain covalent organic framework inorganic semiconductor composite material.

[0007] In the optimized preparation method described above, in step (1), the solvent is n-butanol, and the ratio of indium zinc sulfide to solvent is 35~40mg:1mL.

[0008] In the optimized preparation method described above, the molar ratio of 4,4'-(5,6-difluorobenzo[c][1,2,5]thiadiazole-4,7-diyl)diphenylamine to 2,4,6-trihydroxy-1,3,5-benzyltricarboxaldehyde is 1.4~1.6:1.

[0009] In the optimized preparation method described above, the concentration of acetic acid is 5~6.5 mol / L.

[0010] In the optimized preparation method described above, step (3) involves washing with N,N-dimethylformamide and anhydrous acetone, respectively.

[0011] In the optimized preparation method described above, in step (3), the drying temperature is 55~65℃ and the drying time is 12~18 h.

[0012] In the optimized preparation method described above, the indium zinc sulfide is prepared by the following method: ZnCl2, InCl3 and thioacetamide are added to deionized water and stirred at room temperature to dissolve, thereby obtaining a mixed solution; then the solution is reacted at 170~185℃ for 2~4h; washed and freeze-dried under vacuum to obtain indium zinc sulfide.

[0013] On the other hand, the present invention also provides the application of the above-mentioned covalent organic framework inorganic semiconductor composite material in photocatalytic H2O2 production.

[0014] Compared with the prior art, the beneficial effects of the present invention are: 1. In the covalent organic framework inorganic semiconductor composite material of the present invention, the covalent organic framework material BTTp is loaded on the surface of indium zinc sulfide, which significantly improves the photocatalytic activity for H2O2 production. The loading rate (mass percentage) of the covalent organic framework material is 10~15%, and the catalytic efficiency for H2O2 production from pure water is greatly improved under visible light irradiation.

[0015] 2. This invention employs an in-situ composite method to load the visible-light-responsive covalent organic framework BTTp onto the surface of ZIS nanoclusters, thereby increasing the absorption of the inorganic semiconductor ZIS from 537 nm to 589 nm. This method requires a lower amount of covalent organic framework material, significantly improves the photocatalytic hydrogen peroxide production performance, and substantially reduces the material's production cost. In visible light irradiation and pure water systems, the photocatalytic hydrogen peroxide production rate of the 15-BTTp / ZIS composite photocatalyst reaches as high as 3214.6 µmol / g. -1 .h -1 It is about 4.4 times and 7.3 times higher than BTTp COF and ZIS, respectively. Attached Figure Description

[0016] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 This is a synthetic route diagram of the covalent organic framework inorganic semiconductor composite material according to an embodiment of the present invention; Figure 2Characterization images of the BTTp / ZIS composite material prepared in Example 2 of the present invention, and the BTTp COF and ZIS prepared in Comparative Example 1: (a) PXRD and (b) FT-IR images; Figure 3 The images show the BTTp / ZIS composite material prepared in Example 2 of this invention, along with TEM and EDS distribution diagrams. Figure 4 The UV-Vis absorption spectra of the BTTp / ZIS composite material prepared in Example 2 of this invention, and the BTTp COF and ZIS solids prepared in Comparative Example 1 are shown. Figure 5 This is a comparison chart showing the rate of hydrogen peroxide synthesis from BTTp / ZIS composite materials with different BTTp loadings prepared in Examples 1-3 of this invention. Figure 6 Comparison of catalytic performance of ZIS, BTTp COF prepared in the comparative example and 15-BTTp / ZIS composite material prepared in Example 2: (a) photocatalytic hydrogen peroxide production with light exposure time and (b) photocatalytic hydrogen peroxide production rate.

[0018] Figure 7 Stability and cycling performance of ZIS, BTTp COF prepared in the comparative example, and 15-BTTp / ZIS composite material prepared in Example 2. Detailed Implementation

[0019] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Unless otherwise defined, all technical terms used below have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, all raw materials, reagents, instruments, and equipment used in the present invention are commercially available or can be prepared by existing methods.

[0020] Zinc indium sulfide (ZnIn2S4) (ZIS) is prepared by the following method: 54.5 mg (0.4 mmol) ZnCl2, 176.9 mg (0.8 mmol) InCl3, and 240.4 mg (3.2 mmol) thioacetamide (TAA) were added to 40 mL of deionized water and stirred at room temperature for 30 min until completely dissolved, forming a homogeneous and transparent mixed solution. The mixed solution was transferred to a 100 mL polytetrafluoroethylene reaction vessel and reacted at 180 °C for 3 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, centrifuged, and washed three times with deionized water. Finally, it was dried using a vacuum freeze dryer for 24 h to obtain ZnIn2S4.

[0021] Example 1 A method for preparing a covalent organic framework inorganic semiconductor composite material with photocatalytic properties is as follows: Figure 1 As shown, it includes the following steps: (1) Place 180 mg of zinc indium sulfide (ZIS) and 5 mL of n-butanol in a 10 mL Schlenk tube and sonicate for 10 min; (2) Subsequently, 14.4 mg (0.041 mmol) of 4,4'-(5,6-difluorobenzo[c][1,2,5]thiadiazole-4,7-diyl)diphenylamine (BT-2F) and 5.6 mg (0.027 mmol) of 2,4,6-trihydroxy-1,3,5-benzenetrialdehyde (Tp) were added sequentially. After sonication for 5 min, 0.5 mL of 6 mol / L acetic acid was added, followed by sonication again. After three cycles of freeze-degassing, the tube was sealed and reacted in a 120℃ oven for 72 h. (3) After the reaction is completed and cooled to room temperature, wash twice with DMF and anhydrous acetone respectively, and dry in a vacuum drying oven at 60℃ for 12 h to obtain a brown powder, which is the BTTp-COF / ZIS composite material. The loading rate of the composite material BTTp-COF is 10% (the loading rate refers to the mass fraction of BTTp in the composite material, and the mass of BTTp is expressed as (mass of BT-2F + mass of Tp)), which is denoted as 10-BTTp / ZIS.

[0022] Example 2 A method for preparing a covalent organic framework inorganic semiconductor composite material with photocatalytic properties includes the following steps: (1) Place 170 mg of zinc indium sulfide (ZIS) and 5 mL of n-butanol in a 10 mL Schlenk tube and sonicate for 10 min; (2) Subsequently, 21.6 mg (0.061 mmol) of 4,4'-(5,6-difluorobenzo[c][1,2,5]thiadiazole-4,7-diyl)diphenylamine (BT-2F) and 8.4 mg (0.040 mmol) of 2,4,6-trihydroxy-1,3,5-benzenetrialdehyde (Tp) were added sequentially. After sonication for 5 min, 0.5 mL of 6 mol / L acetic acid was added, followed by sonication again. After three cycles of freeze-degassing, the tube was sealed and reacted in a 120℃ oven for 72 h. (3) After the reaction is completed and cooled to room temperature, wash twice with DMF and anhydrous acetone respectively, and dry in a vacuum drying oven at 60℃ for 12 h to obtain a brown powder, which is the BTTp-COF / ZIS composite material. The loading rate of BTTp-COF is 15%, which is denoted as 15-BTTp / ZIS.

[0023] Example 3 A method for preparing a covalent organic framework inorganic semiconductor composite material with photocatalytic properties includes the following steps: (1) Place 160 mg of zinc indium sulfide (ZIS) and 5 mL of n-butanol in a 10 mL Schlenk tube and sonicate for 10 min; (2) Subsequently, 28.8 mg (0.081 mmol) of 4,4'-(5,6-difluorobenzo[c][1,2,5]thiadiazole-4,7-diyl)diphenylamine (BT-2F) and 11.2 mg (0.053 mmol) of 2,4,6-trihydroxy-1,3,5-benzenetrialdehyde (Tp) were added sequentially. After sonication for 5 min, 0.5 mL of 6 mol / L acetic acid was added, followed by sonication again. After three cycles of freeze-degassing, the tube was sealed and reacted in a 120℃ oven for 72 h. (3) After the reaction is completed and cooled to room temperature, wash twice with DMF and anhydrous acetone respectively, and dry in a vacuum drying oven at 60℃ for 12 h to obtain a brown powder, which is the BTTp-COF / ZIS composite material. The loading rate of BTTp-COF is 20%, which is denoted as 20-BTTp / ZIS.

[0024] Comparative Example Preparation of BTTp-COF: 16.0 mg (0.045 mmol) of 4,4'-(5,6-difluorobenzo[c][1,2,5]thiadiazole-4,7-diyl)diphenylamine (BT-2F), 6.3 mg (0.03 mmol) of 2,4,6-trihydroxy-1,3,5-benzenetrialdehyde (Tp) and 1.0 mL of n-butanol were added to a glass tube and ultrasonically dispersed for 10 min. Then, 0.10 mL of 6 mol / L acetic acid solution was added, followed by ultrasonic mixing again. The mixture was subjected to three cycles of freeze-degassing and then sealed, and reacted in an oven at 120 °C for 72 h. After the reaction was completed, the mixture was cooled to room temperature and washed 2-3 times by centrifugation with N,N-dimethylformamide (DMF) and anhydrous acetone, and dried in a vacuum drying oven at 60 °C for 12 h to obtain the BTTp-COF material, denoted as BTTp.

[0025] Figure 2The images show the BTTp / ZIS composite material prepared in Example 2 of this invention, and the COF and ZIS dePXRD and FT-IR spectra of BTTp and ZIS prepared in Comparative Example 1. Figure 3 The figures show the TEM and EDS distributions of the BTTp / ZIS composite material prepared in Example 2. As can be seen from the figures, the BTTp-COF / ZnIn2S4 composite material of this invention contains both BTTp-COF and ZnIn2S4, indicating that the two materials were successfully composited, with BTTp-COF loaded on ZnIn2S4.

[0026] Figure 4 The figure shows the solid-state UV-Vis absorption spectrum of the material. As can be seen from the figure, the present invention increases the absorption of the inorganic semiconductor ZIS from 537 nm to 589 nm.

[0027] Photocatalytic performance of test example materials Test method: The performance of photocatalytic synthesis of hydrogen peroxide was tested in a quartz reactor. 5 mg of photocatalyst was added to 50 mL of water and sonicated for 5 min to obtain a uniformly dispersed reaction solution. The reaction solution was poured into the reactor, and oxygen (O2) was continuously introduced into the reaction system for 30 min under dark conditions to allow the photocatalyst to reach oxygen adsorption-desorption equilibrium. A xenon lamp (300 W) equipped with a λ ≥ 420 nm filter was used as the light source to simulate visible light irradiation, and the temperature of the reaction system was maintained at 25℃ using a circulating condenser. Every 15 min, 1 mL of the reaction solution was drawn from the reactor, filtered through a 0.22 μm aqueous filter to remove the solid catalyst, and 1 mL of the test solution was mixed thoroughly with 1 mL of 1 M Ce(SO4)2 solution. The remaining Ce was then measured using a UV-Vis spectrophotometer. 4+ The concentration of H2O2 generated was calculated using a standard curve.

[0028] Tested the different loading rates prepared in Examples 1-3 respectively. x -BTTp / ZIS ( x The rate of hydrogen peroxide synthesis from composite materials (10%, 15%, 20%) under visible light irradiation was measured. The test results are as follows: Figure 5 As shown, the addition of BTTp significantly improves the photocatalytic synthesis rate of hydrogen peroxide from ZIS, and the photocatalytic synthesis rate of hydrogen peroxide from 15-BTTp / ZIS reaches its peak at a loading of 15 wt%. Figure 6 As shown, the hydrogen peroxide formation rate of BTTp COF is relatively low, at 724 µmol·g. -1 .h -1 The hydrogen peroxide formation rate of ZIS was also very low, at 439.2 µmol·g. -1.h -1 However, the photocatalytic hydrogen peroxide generation rate of the 15-BTTp / ZIS composite material reached as high as 3214.6 µmol·g. -1 .h -1 The loading values ​​were approximately 4.4 times and 7.3 times higher than those of BTTp-COF and ZIS, respectively. This demonstrates that an appropriate loading of BTTp-COF can significantly promote the photocatalytic reaction.

[0029] The photostability and repeatability of the samples were evaluated through a long-term cyclic hydrogen peroxide generation experiment. The results are as follows: Figure 7 As shown, the photocatalytic hydrogen peroxide production rates of ZIS, BTTp COF, and 15-BTTp / ZIS did not change significantly over four cycles lasting 4 hours, indicating that 15-BTTp / ZIS has excellent photostability and reproducibility in the photocatalytic hydrogen peroxide production reaction.

[0030] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A covalent organic framework inorganic semiconductor composite material with photocatalytic properties, characterized in that, The composite material is a BTTp-COF / ZnIn2S4 composite material, wherein the mass percentage of ZnIn2S4 in the composite photocatalytic material is 80-90%, and the mass percentage of BTTp-COF is 10-20%. The raw materials for the synthesis of BTTp-COF include 4,4'-(5,6-difluorobenzo[c][1,2,5]thiadiazole-4,7-diyl)diphenylamine and 2,4,6-trihydroxy-1,3,5-benzenetrialdehyde.

2. The covalent organic framework inorganic semiconductor composite material according to claim 1, characterized in that, The composite photocatalytic material contains 85% ZnIn2S4 by mass and 15% BTTp-COF by mass.

3. A method for preparing a covalent organic framework inorganic semiconductor composite material as described in claim 1 or 2, characterized in that, Includes the following steps: (1) Disperse indium zinc sulfide and solvent by ultrasonication for 5-15 min; (2) Add 4,4'-(5,6-difluorobenzo[c][1,2,5]thiadiazole-4,7-diyl)diphenylamine and 2,4,6-trihydroxy-1,3,5-benzyltricarboxaldehyde in sequence, continue sonication for 5~10 min, then add acetic acid and sonicate to mix; after multiple cycles of freezing-degassing, react in a vacuum environment at 110~130℃ for 65~75 h; (3) After the reaction is complete, wash and vacuum dry to obtain covalent organic framework inorganic semiconductor composite material.

4. The preparation method according to claim 3, characterized in that, In step (1), the solvent is n-butanol, and the ratio of indium zinc sulfide to solvent is 35~40 mg : 1 mL.

5. The preparation method according to claim 3, characterized in that, The molar ratio of 4,4'-(5,6-difluorobenzo[c][1,2,5]thiadiazole-4,7-diyl)diphenylamine to 2,4,6-trihydroxy-1,3,5-benzyltricarboxaldehyde is 1.4~1.6:

1.

6. The preparation method according to claim 3, characterized in that, The concentration of the acetic acid is 5~6.5 mol / L.

7. The preparation method according to claim 3, characterized in that, In step (3), N,N-dimethylformamide and anhydrous acetone are used for washing.

8. The preparation method according to claim 3, characterized in that, In step (3), the drying temperature is 55~65℃ and the drying time is 12~18 h.

9. The preparation method according to claim 3, characterized in that, The indium zinc sulfide was prepared by the following method: ZnCl2, InCl3 and thioacetamide were added to deionized water and stirred at room temperature to dissolve them, resulting in a mixed solution; then the solution was reacted at 170~185℃ for 2~4 h; after washing, it was freeze-dried under vacuum to obtain indium zinc sulfide.

10. The application of the covalent organic framework inorganic semiconductor composite material as described in any one of claims 1 or 2 in the photocatalytic production of H2O2.